Education as a Phenomenological Experience - Jiménez, Marco Antonio; Valle Vázquez, Ana María (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Our document intends to re-flect on what can be called educational experience based on a phenomenological look. If we accept that phenomenology is the reflection about the experience produced by the unveiling of the own experience, we could re-consider, re-signify the contents of the awareness about education. There is awareness about experience because there is re-flection on it. According to Husserl, through reflection we apprehend subjective experiences that become conscious for us, in so far as they appear; this is why every single conscious experience is also called phenomena. It is in this regard that phenomenology allows us to see the otherness of the reality, in this case at hand, of education. It allows having a “way of seeing” through which what has been placed in parentheses is seen, what has been suspended, the epoché of the world naturally educational, such as given meanings as they are given, so this world will have a new meaning.